Ultrasonographic features of limited joint mobility in patients with type 2 diabetes mellitus. Almanzor Aguinaga-Asenjo Hospital. EsSalud, Chiclayo, 2009-2010 - Fernández Mogollón, Jorge Luis (2012)
Objective: The main purpose of this study was to measure the thickness of the flexor tendons using ultrasonography of the hands in type 2 diabetic patients with limited joint mobility in Almanzor Aguinaga- Asenjo Hospital, and to compare these measurements with those recorded in type 2 diabetic patients with no limited joint mobility. Material y Method: Forty-four volunteer patients were recruited in our hospital between December 2009 and March 2010, and they were divided in two groups: those with limited joint mobility and those without this feature. The praying hand maneuver was performed in every patient, afterwards, the painted hand test was performed, in order to assess the degree of functional limitation, and then the ultrasonography examination was performed in the dominant hand in order to determine if there was (>1 mm) thickening of the tendon sheaths. Results: There was thickening (>1 mm) in the flexor tendon sheaths in 68,2% of type 2 diabetic patients with limited joint mobility, while adequate thickness (<1 mm) of the flexor tendon sheaths was found in 100% of type 2 diabetic patients with no limited joint mobility. Conclusions: Flexor tendon sheath thickening is more evident in type 2 diabetic patients with limited joint mobility compared to those patients with no limited joint mobility.